Maxillary Calcifying Epithelial Odontogenic Tumour - Souvagini Acharya; Nilamadhab Prusty; Choubarga Naik; Koushal Kumar (Journal of Nepal Medical Association, 2016)
The calcifying epithelial odontogenic tumor is a benign, locally invasive, slow-growing neoplasm occurring as intraosseous (94%) and extraosseous (6%) variants and with a frequency of 1-2%. Extraosseous variant is diagnosed slightly earlier than the intraosseous type. The intraosseous CEOT shows a maxilla:mandible site ratio of 1:2 and are mainly located in the premolar/molar region. Histologically, the CEOT is characterized by the occurrence of sheets, nests and masses of polyhedral, eosinophilic epithelial cells which may show cellular abnormalities including giant cell formation and nuclear pleomorphism. Some cells increase in size andproducea homogeneous, eosinophilic, 'amyloid-like' substance which may become calcified and which may be liberated as the cells break down. Enucleation with amarginof macroscopically normal tissue is the recommended treatment for CEOT involving the mandible. Maxillary CEOT are treated more aggressively, as they tend to grow more rapidly and do not usually remain well confined. Keywords: calcifying epithelial odontogenictumor; Pindborgtumor;hemimandibulectomy. | PubMed